高中生持續參與遊戲意圖之研究：以 3D 摩托車數位遊戲為例 High School Students’ Continual Participation in Game Intentions: A Case Study of 3D Motorcycle Digital Gaming Learnin - 張聖淵 Sheng-Yuan Chang; 詹勳從 Shiun-Taung Jan (Journal of Research in Education Sciences, 2019)
本研究使用平板電腦進行「3D 摩托車」數位遊戲，讓未參加過摩托車駕照考試的技術型高中學生模擬騎乘摩托車情境，其中遊戲內容設計了在道路上騎乘摩托車的法規規定、正確騎乘行為，以及其他騎乘行為之干擾，讓使用者學習騎乘技巧與交通法規。進行 3D 摩托車數位遊戲後，再以問卷調查研究對象在遊戲認知疲乏、遊戲焦慮、學習價值及持續參與遊戲意圖構面之相關性。本研究結果顯示，參與 3D 摩托車數位遊戲的使用者，其在遊戲認知疲乏與學習價值呈顯著負相關；遊戲焦慮與學習價值呈顯著正相關；學習價值和持續參與遊戲意圖呈顯著正相關。具體而言，本研究結果發現，若 3D 摩托車數位遊戲能降低使用者遊戲認知疲乏及遊戲焦慮，便能提升使用者之學習價值，進而引發其持續參與遊戲意圖。 The “3D Motorcycle” digital game is designed to regulate the rules of riding a motorcycle on the road for players to familiar with the rules of transportation by simulating their cognitive and affective perception to explore the effect of this design. After conducting “3D Motorcycle” game playing, a questionnaires were delivered. The relevance of cognitive failure and anxiety, learning value perception and continuance intention. The findings of this study indicated that cognitive failure was negatively related to learning value perception, but gameplay anxiety was positively related to; the perception of learning value was positively related to continuance intention to play this “3D Motorcycle” game. The implication of this study suggested that those educational institutes of transportation safety can apply this “3D Motorcycle” game to enhance the perception of transportation rules to reduce future use real motorcycle accidents.